The Impact of Ownership Structure and Corporate Social Responsibility on Profitability and Firm Value of Companies Listed on The Indonesia Stock Exchange: An Analysis of Recent Data (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to analyze the impact of ownership structure and corporate social responsibility (CSR) on the profitability and firm value of companies listed on the Indonesia Stock Exchange. Utilizing the latest data from annual reports published between 2021 and 2023, this research employs multiple regression analysis to test the proposed hypotheses. The findings reveal that (1) ownership structure has a positive and significant effect on the firm's profitability, indicating that diversified ownership can enhance financial performance; (2) corporate social responsibility positively and significantly influences profitability, suggesting that companies engaged in CSR initiatives tend to be more profitable; (3) ownership structure does not have a significant impact on firm value, indicating that other factors may be more dominant in market valuation; (4) corporate social responsibility positively and significantly affects firm value, implying that investment in CSR can enhance positive investor perceptions; and (5) specifically, corporate social responsibility has a positive and significant impact on the firm value in the manufacturing sector listed on the Indonesia Stock Exchange. These findings emphasize the importance of sound ownership strategies and a commitment to social responsibility as key factors in enhancing both profitability and firm value.